ADVANTAGES OF USING TRANSLATION, PARAPHRASING, AND PODCASTS TO IMPROVE NATURAL WRITING SKILLS - Suseno, Edy (Sanata Dharma University Yogyakarta, 2024)
Most EFL students find it difficult to articulate themselves clearly in written assignments. To overcome those flaws, twenty-five college students enrolled in the program. The WhatsApp program was employed as a classroom tool because of online learning. The teacher modified the audio materials in an attempt to strengthen the pupils' inadequate writing abilities. The students observed the native speakers' use of grammar in their transcribing and used that to understand grammar usage. To help with vocabulary development, the students also translate it into their native tongue. The students recount the podcasts' material to improve their speaking flow. The information the students learned from the podcast materials was applied to the description of images. Students utilized paraphrasing applications to complete the proofreading assignments. It is a procedure to hone their writing abilities. It is discovered by qualitative data analysis that students can successfully produce natural writing by using paraphrasing tools, translation services, and podcasts. Instructors can teach pertinent subjects with the use of this kind of material. It is also causing other researchers to become aware of more pertinent discoveries.